Intensitas Bermedia Sosial dan Minat Muslim Urban Berhijrah: Analisis Followers Akun Instragram @Surabayahijrah - Irawan, Rahmat Edi; Palupi, Merry Fridha Tri; Putro, Taufan Aji Santoso (Jurnal Komunikasi Islam, 2019)
This study aims to measure the effect of the intensity of accessing Instagram account access @surabayahijrah on followers' interest to hijrah (individual muslim shifts towards a more religious way of life). This article is the result of a correlational quantitative study with the number of sample 100 followers of Instagram account @Surabayahijrah who live in Surabaya. The results have shown that r squared is 0.1186 which means that there was an influence of Instagram account access @ surabayaahijrah of 11.86% on the interest of hijrah and the rest was another factor outside of the research about 88.14%. Partial test results (t) also indicated that the t-value of 2.066> t-value of 1.667, which means that there was an influence of partial access to the account @surabayahijrah with a significance value of 0.041 which is less than the specified significance value of 0.1.